An automated software team formation based Belbin team role using fuzzy technique - Abdulrahman, Bikhtiyar Hasan (2016)
In software engineering (SE), team plays an important role in determining the project success. To ensure the optimal outcome of the project the team is working on, it is essential to ensure that the team comprises of the members with right characteristics. In a team assigning the right role to each team member in order to make certain that the most appropriate individuals are chosen for specific tasks and their efforts contribute maximum to the overall team performance. One of the prevalent team roles is Belbin team role. Belbin developed this theory for formation a successful team. This theory is centered on the team roles and how they should be matched in order to avoid conflicts and build sound teams that are optimally managed. Therefore, the main aim of this study is to develop an automated software team formation method based on Belbin Team Role by using a Fuzzy technique. Fuzzy technique was chosen because it allows analyzing of imprecise data and classifying selected criteria. In this study, two roles in Belbin Team role, which are Shaper (Sh) and Plant (Pl) were chosen to assign the specific role in software team – team leader and programmer, respectively. These roles were chosen because the combination of these roles is able to determine effective team members in SE team. The proposed automated software team formation was then evaluated using an expert review. The participants consist of 12 software developers from Asiacell Telecommunication Company in Kurdistan Region Government of Iraq (KRG). The results demonstrate that the method is useful to be used for forming SE team in industrial setting. The proposed automated software team formation can serve as a useful tool for managers when assigning new team members to a software project. In addition, by using the proposed method, it can help decision makers specifically managers to form effective and equal teams. Effective and equal teams can have an equal chance to experience good team work and thus, to be a successful team.